Bridging the lapses : the use of translator’s notes in fansubbing, a case study on Bangtan Subs - Lakner, Laura (My University, 2022)
Fansubbing, a form of fan translation, is the subtitling of audiovisual media performed by fans of that media. Products of fansubbing, fansubs, sometimes contain translator's notes (abbreviated to T/N) which are situated on the upper part of the screen and appear simultaneously with the subtitles on the bottom. A form of norm-governed translation strategy use, notes from the translator usually explain some part of the translation or offer additional information that aids the target reader's understanding. This thesis examines the use of translator's notes in fansubs produced by the fan translation team BangtanSubs in fansubs about the K-Pop group BTS. The study aims to ascertain firstly what kinds of aspects translator's notes attempt to explain and at what frequency, and secondly what the fan translators' motivations behind using translator's notes are. A collection of translator's notes and a questionnaire filled out by fan translators are analyzed to answer these questions. The theories of Leppihalme as refined by Bodó are utilized in creating a taxonomy by which the content of translator's notes can be categorized and analyzed. The analysis of the notes' function and frequency in occurrence informs the understanding of the questionnaire results. Translator's notes were found to explain extralinguistic aspects of the source text the most, and the reasoning behind using them lay in the translators' assumption that they were supplementing the target reader's knowledge on the subject. Additionally, a translator’s note was reported to be used when the translation of a specific part of the source text would have been challenging either in terms of subtitle space or without sacrificing faithfulness to the original text. The present study focuses comprehensively on the use of translator’s notes in fansubbing, a topic still fairly under-researched. Other avenues for possible further research would be the comparisons of professional subtitles and fansubs of the same media and a detailed descriptive study on the guidelines used by organized fan translation networks.
Keywords: fan translation, fansubbing, translator’s notes, translational norms, paratext